Offshoring Business Processes: An Accounting Firm Graduate Perspective - Caratti , Silvia Claudia (Curtin University, 2018)
This exploratory thesis examines how the adoption of offshoring in accounting firms through differing structures affects the employability of Australian accounting domestic graduates. Adopting a constructivist approach, the thesis concludes that offshoring negatively impacts domestic graduates’ recruitment, roles and training. Contributions of this thesis include highlighting the contextual impact that offshoring is having on accounting graduate employability whilst emphasising the importance of collaboration between academia and the profession in relation to domestic accounting graduates.